Use of evidence to promote inclusive education development commentary on Mel Ainscow. Promoting inclusion and equity in education: lessons from international experiences - Michel Knigge (Taylor & Francis Group, 2020)
In his essay, Mel Ainscow looks at inclusion and equity from an international perspective and makes suggestions on how to develop inclusive education in a 'whole-system approach'. After discussing different conceptions of inclusion and equity, he describes international policies which address them. From this international macro-level, Ainscow zooms in to the meso-level of the school and its immediate environment, defining dimensions to be considered for an inclusive school development. One of these dimensions is the 'use of evidence'. In my comment, I want to focus on this dimension and discuss its scope and the potential to apply it in inclusive education development. As a first and important precondition, Ainscow explains that different circumstances lead to different linguistic uses of the term 'inclusive education'. Thus, the term 'inclusive education' does not refer to an identical set of objectives across countries, and neither does the term 'equity'.